Give chance a chance - Nachury, Maxence V. (The American Society for Cell Biology, 2011)
How did I get to become a cell biologist? Or, more generally, why do things happen the way they do? The answer provided by the philosopher Democritus and later adopted by Jacques Monod is “everything existing in the universe is the fruit of chance and necessity.” While I read Monod's book Chance and Necessity as an undergraduate student, little did I appreciate the accuracy of this citation and how much of my scientific trajectory would be guided by chance.